Getting Started with BizTalk Services. - Bharathy, Karthik (Professional expertise distilled, 2014)
A practical book that acts as a clear and concise introduction to BizTalk Services. Full of real-world scenarios, each area of BizTalk Services is explained in detail, essentially enabling you to smoothly design your own integration solutions with minimal effort. This book is intended for those who want to understand BizTalk Services, what it can do, and how to build integration solutions using it in their organizations. If you are a developer, architect, or project manager, this book will quickly get you acquainted with this powerful cloud integration technology. It would be helpful to have s.